2018
DOI: 10.1146/annurev-pharmtox-010617-052645
|View full text |Cite
|
Sign up to set email alerts
|

Development and Therapeutic Potential of Small-Molecule Modulators of Circadian Systems

Abstract: Circadian timekeeping systems drive oscillatory gene expression to regulate essential cellular and physiological processes. When the systems are perturbed, pathological consequences ensue and disease risks rise. A growing number of small-molecule modulators have been reported to target circadian systems. Such small molecules, identified via high-throughput screening or derivatized from known scaffolds, have shown promise as drug candidates to improve biological timing and physiological outputs in disease model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 171 publications
0
96
0
1
Order By: Relevance
“…Recent studies imply that the growing epidemic of metabolic diseases is strongly associated with circadian misalignments, which many of us experience with increasing frequency, related for instance to acute jetlag, chronic shifted work schedules, or other types of “social jetlag.” If future translational studies would confirm the link between T2D and circadian clock perturbations in humans, as it has been demonstrated in rodent models, this association will open new avenues for the treatment of metabolic diseases. Indeed, clock modulators, small molecules capable of restoring disrupted circadian oscillators, in particular the group of amplitude‐enhancing small molecules (CEMs), are likely representing important future therapeutic targets for the treatment of metabolic disorders If future studies confirm that obesity and type 2 diabetes are associated with circadian clock perturbations in humans, this will open new avenues for the treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies imply that the growing epidemic of metabolic diseases is strongly associated with circadian misalignments, which many of us experience with increasing frequency, related for instance to acute jetlag, chronic shifted work schedules, or other types of “social jetlag.” If future translational studies would confirm the link between T2D and circadian clock perturbations in humans, as it has been demonstrated in rodent models, this association will open new avenues for the treatment of metabolic diseases. Indeed, clock modulators, small molecules capable of restoring disrupted circadian oscillators, in particular the group of amplitude‐enhancing small molecules (CEMs), are likely representing important future therapeutic targets for the treatment of metabolic disorders If future studies confirm that obesity and type 2 diabetes are associated with circadian clock perturbations in humans, this will open new avenues for the treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clock modulators, small molecules capable of restoring disrupted circadian oscillators, in particular the group of amplitude-enhancing small molecules (CEMs), are likely representing important future therapeutic targets for the treatment of metabolic disorders. 128 " If future studies confirm that obesity and type 2 diabetes are associated with circadian clock perturbations in humans, this will open new avenues for the treatment of these diseases.…”
Section: Cell-autonomous Circadian Oscillations In the Endocrine Pancmentioning
confidence: 99%
“…42,161,163 Moreover, an important perspective for a novel therapeutic approach would be to utilize small clock modulator molecules for restoring a disrupted oscillator function in order to manage these diseases. 208,209 Given the raising awareness about the significance of circadian misalignment for human pathologies, advancing our knowledge on human molecular clocks and their link to physiology bears the benefit of immediate clinical implication.…”
Section: Discussionmentioning
confidence: 99%
“…135 In several recent studies, such compounds, either naturally occurring or synthetic, have shown promising efficacies in rodent models for various diseases including metabolic disease, mood disorder and ageing. 135,136 For emerging clock-related diseases such as pain, establishment of model systems will allow testing of novel therapeutics. As mentioned above, the critical next step is to identify the key circadian characteristic or factors that may be causal or serve as biomarkers for the disease.…”
Section: Chronotherapy For Headache Disordersmentioning
confidence: 99%